Comparison of Learning Strategies for Mathematics Achievement in Turkey with Eight Countries - Kilic, Serpil; Cene, Erhan; Demir, Ibrahim (EDAM, 2012)
The purpose of this study was to examine learning strategies accounted for mathematics achievement across Turkey and neighboring countries. Turkey, Bulgaria, Greece, Azerbaijan, Russian Federation, Israel, Serbia, Romania and Jordan were involved in Programme for International Student Assessment (PISA 2009) study. Since other neighbors of Turkey were not participated in PISA study, they were not evaluated. In this study, PISA mathematics test score and questionnaire responses of 17224 students aged 15 year-old were analyzed via multilevel models. Three-level model was used to estimate coefficients and to model differences across countries and schools. At the first level, gender, socio-economic status (SES), elaboration, memorization, control strategy, home educational resources and cultural possession were considered and it was determined that all the variables except memorization strategy had positive effect on students' mathematics achievement. School size and student-teacher ratio were considered at the second level and gross domestic product (GDP) was considered at the third level. At the second and third level, it was revealed that all the variables except student-teacher ratio had a positive effect on students' achievement. The signs of significant coefficients on students' mathematics scores for each country were shown by using two-level regression. These results were crucially important for the education system to be effective in terms of increasing students' mathematics achievement due to the fact that changing school climate and improving the learning strategies are much easier to achieve than changing other variables affecting students' performance.
Keywords: Learning Strategies; Multilevel Models; Mathematics Achievement; Neighbor Countries; PISA; SCHOOL; SCIENCE; PERFORMANCE; RESOURCES; STUDENTS; GENDER; SIZE; Education & Educational Research